2006
DOI: 10.1111/j.1471-0528.2006.00865.x
|View full text |Cite
|
Sign up to set email alerts
|

Mode of delivery is associated with maternal and fetal endocrine stress response

Abstract: Objective To determine whether mode of delivery is associated with the endocrine stress response in mother and child.Design Prospective observational study.Setting Tertiary care centre, University hospital.Population A total of 103 nulliparous women with uncomplicated singleton pregnancies at term undergoing either spontaneous labour for vaginal delivery or delivering by caesarean section without labour. Thirty women delivered vaginally without any pain relief, 21 women delivered vaginally with epidural anaest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
124
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(141 citation statements)
references
References 24 publications
11
124
1
5
Order By: Relevance
“…Even more, our study points the physiological maternal biochemical and hormonal response to short term fasting performs as a "stability glycemic mechanism", despite the mild "stress" effect observed on the cortisol levels changes. Albeit the wide variability in the hormonal levels reported in the literature and the diurnal rhytms the ma- ternal and umbilical blood levels in our study were comparable with the literature and unaffected by the mode of delivery [21]. Maternal fasting did not result in any hypoglycemic state and was characterized by significantly lower insulin levels.…”
Section: Discussionsupporting
confidence: 86%
“…Even more, our study points the physiological maternal biochemical and hormonal response to short term fasting performs as a "stability glycemic mechanism", despite the mild "stress" effect observed on the cortisol levels changes. Albeit the wide variability in the hormonal levels reported in the literature and the diurnal rhytms the ma- ternal and umbilical blood levels in our study were comparable with the literature and unaffected by the mode of delivery [21]. Maternal fasting did not result in any hypoglycemic state and was characterized by significantly lower insulin levels.…”
Section: Discussionsupporting
confidence: 86%
“…During VD, stress increases the plasma levels of catecholamines (14)(15)(16) . This increment may also activate the corneal endothelial pump system and result in thinner corneas in vaginally-delivered infants.…”
Section: Introductionmentioning
confidence: 99%
“…Results of the majority of these studies suggested a tendency toward increased lymphocyte subset counts in neonates born by vaginal delivery compared with neonates born by caesarean delivery (9 -11,13-16). The endocrine-metabolic variations during a stressful delivery, particularly hypoxia and the increase of catecholamines and cortisol, were considered as the main cause of these effects (17)(18)(19). Additionally to this stress concept, adverse Apgar scores and umbilical cord blood pH, both results of perinatal hypoxia, are thought to influence lymphocyte subset counts at birth (9,20 -22).…”
mentioning
confidence: 99%